Peran Ekstrakurikuler Kepramukaan Dalam Pembentukan Karakter Siswa di Sekolah Dasar - Anisa Siregar; Rianta Dika Malau; Rohyana Salmi Ritonga; Fajar Sidik Siregar (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to determine the role of scouting extracurricular activities in forming students' independent personalities in elementary schools. The method used is descriptive qualitative with two types of literature and a literature review. The data collection technique uses the documentation method. The source of data obtained in this research is from previous journals which were created by searching for journals or books in several electronic media such as the internet, digital libraries and other collections which were then selected and analyzed further by researchers. The results of the research analysis show that Scouts activities make a positive contribution to shaping the character of independent students such as increasing self-confidence, courage, responsibility, discipline and problem-solving skills. Through various challenging and fun activities, students are trained to take initiative, think creatively and not give up easily. Support from Scout leaders and schools also plays an important role in creating a favorable environment for the development of the independent personality of students. This research concludes that out-of-school Scouting can be an effective way of instilling the values of self-confidence in primary school students.